2022
DOI: 10.1016/j.jad.2021.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between working stress and anxiety of medical workers in the COVID-19 situation: A moderated mediation model

Abstract: Background The COVID-19 pandemic has brought a lot of working stress to medical workers and has a certain impact on their mental health. Working stress is closely related to the increase in anxiety, but few studies have explored whether their relationship will be affected by positive psychological factors in the special situation. Methods 798 medical workers were investigated online after the outbreak of the COVID-19 (10 February to 1 March 2020) in China. The relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Our findings significantly link with previous studies. 30,31 For example, a multicenter online survey conducted in China to assess the mental health of healthcare professionals revealed that 44.7% had signs of anxiety. [32][33][34] On the other hand, only 15.7% of the respondents in global research carried out in Singapore and India displayed anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings significantly link with previous studies. 30,31 For example, a multicenter online survey conducted in China to assess the mental health of healthcare professionals revealed that 44.7% had signs of anxiety. [32][33][34] On the other hand, only 15.7% of the respondents in global research carried out in Singapore and India displayed anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Every day, the Xiangyang Central Hospital, the largest grade-A hospital in the Northwest Hubei province, more than 200 patients with fever were received daily. Working stress may have a direct effect on anxiety and an indirect effect on anxiety through a sense of control ( Ripp et al, 2020 ; Saffari et al, 2021 ; Hou et al, 2022 ). As the number of people infected with suspected or confirmed COVID-19 rises, healthcare workers face not only increased workloads but also the risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…15 Sağlık anksiyetesinin artması da Covid-19 kontrolü algısını olumsuz etkilemektedir. 16 Bu bağlamda kontrol algısı fazla olan bireylerin daha az anksiyete deneyimledikleri ve Covid-19 kurallarına daha çok uydukları belirlenmiştir. 16,17 Bu kapsamda bu araştırma ile pandemi sürecinde hemodiyaliz tedavisi alan hastaların yaşadıkları anksiyete ile Covid-19'un kontrolü algısı arasındaki ilişkiyi belirlemek amaçlanmıştır.…”
Section: Introductionunclassified